Home‐ and Community‐Based Occupational Therapy Improves Functioning in Frail Older People: A Systematic Review. Issue 8 (3rd April 2017) - De Coninck, Leen; Bekkering, Geertruida E.; Bouckaert, Leen; Declercq, Anja; Graff, Maud J. L.; Aertgeerts, Bert
Abstract : Objectives: The objective is to assess the effectiveness of occupational therapy to improve performance in daily living activities in community‐dwelling physically frail older people. Design: We conducted a systematic review and meta‐analysis. We included randomized controlled trials reporting on occupational therapy as intervention, or as part of a multidisciplinary approach. This systematic review was carried out in accordance with the Cochrane methods of systematic reviews of interventions. Measurements: Meta‐analyses were performed to pool results across studies using the standardized mean difference. The primary outcome measures were mobility, functioning in daily living activities, and social participation. Secondary outcome measures were fear of falling, cognition, disability, and number of falling persons. Results: Nine studies met the inclusion criteria. Overall, the studies were of reasonable quality with low risk of bias. There was a significant increase in all primary outcomes. The pooled result for functioning in daily living activities was a standardized mean difference of −0.30 (95% CI −0.50 to −0.11; P  =   .002), for social participation −0.44 (95% CI −0.69, −0.19; P  =   .0007) and for mobility −0.45 (95% CI −0.78 to −0.12; P  =   .007). All secondary outcomes showed positive trends, with fear of falling being significant. No adverse effects of occupational therapy were found. Conclusion: There is strong evidence that occupational therapy improves functioning in community‐dwelling physically frail older people.